An analysis of migrant health policies in Iran - Kanishka Ghiasi; Ali Mohammad Mosadeghrad; Hossein Dargahi; Ebrahim Jaafaripooyan (Health Research Policy and Systems)
Abstract Introduction Migrant health has emerged as a critical global public health issue, necessitating effective policies to address the needs of this vulnerable population. Iran, hosting over 4.5 million migrants – many undocumented – faces significant challenges in ensuring equitable healthcare access. Despite existing policies, implementation gaps persist, exacerbating health disparities. This study analyzes Iran’s migrant health policies, identifies challenges and proposes effective solutions. Methods This qualitative study involved semi-structured interviews with 38 stakeholders, including policymakers, managers, healthcare providers, migrant health experts and migrants themselves, selected through purposeful and snowball sampling. Data were triangulated with a review of 15 policy documents. Guided by the Integrated Policy Analysis Framework, the study focused on four phases: preparation, formulation, implementation and evaluation. Data analysis followed Ritchie and Spencer’s framework analysis method, ensuring systematic categorization and thematic interpretation. Results The analysis generated 49 codes, grouped into 10 sub-themes and four main themes aligned with the policy analysis framework. Key findings revealed persistent challenges across all phases: (1) policy preparation was hindered by the absence of a formal governance structure, such as the lack of a specific committee within the Ministry of Health and Medical Education for migrant health policies, and insufficient stakeholder involvement; (2) policy formulation suffered from selective health priorities, significant data gaps and the exclusion of undocumented migrants from legal coverage; (3) policy implementation faced financial constraints, insurance disparities and systemic barriers, including e-prescription requirements tied to Iranian IDs; and (4) policy evaluation lacked formal mechanisms for monitoring and assessment, highlighting the need for standardized metrics and accountability frameworks. Conclusions Addressing migrant health in Iran requires a multi-faceted approach that prioritizes stakeholder engagement, robust data collection and inclusive implementation strategies. Establishing dedicated committees, improving data accuracy and ensuring equitable access to health services are critical steps. By implementing these recommendations, Iran can enhance health outcomes for migrants, promote public health and foster social cohesion. This study provides a foundation for evidence-based policy reforms to address the unique health needs of migrant populations.